Vincetoxicum (Apocynaceae: Asclepiadoideae) in Taiwan: Two new combinations and a new record - Hsu, Tian-Chuan; Huang, Wei-Jie; Chung, Shih-Wen (Phytotaxa, 2021)
The genus Vincetoxicum Wolf (1776: 130) was recently redefined by Liede-Schumann & Meve (2018) to include Tylophora Brown (1810: 460) and allied genera on the basis of morphological and molecular evidence (Liede-Schumann et al. 2012, 2016). As Vincetoxicum has not been recognized in regional floristic treatments (e.g. Li et al. 1995; Lu et al. 1998; Lin & Chung 2017), we herein provide a brief account of the ten species currently known in Taiwan (Fig. 1), with two necessary new combinations for Tylophora sui Tseng & Chao (2011: 162) and T. taiwanensis Hatusima (1963: 10). Additionally, Vincetoxicum fordii (Hemsley 1889: 106) Kuntze (1891: 424) was discovered during our recent field investigation and is reported here as a newly recorded species of Taiwan. A key to the species is also provided as below to aid their identification.